Addressing Instability in Afghani (Afghan Currency): Exploring the Strategies for Achieving Stability - Seerat, Dr. Abdul Hameed; Stanikzai, Irfan Ullah; Aryan, Fawad (Society & Sustainability, 2023)
The study aims to explore the monetary policy of the Afghanistan Bank, the instability of the Afghan currency, and the causes and strategies for achieving stability for the Afghan currency. A qualitative approach was used to gain an in-depth knowledge of the issues. By using a semi-structured interview, the professional participants were selected through the snowball sampling technique. All interviews were audio-taped, transcribed, and analyzed through a thematic analysis framework. The study addressed instability in the Afghani currency and its causes including trade imbalance in favor of imports, smuggling of the foreign reserve, lack of foreign aid, lack of control of the natural resources, lack of foreign investment, inefficiency in monetary and fiscal policy, fluctuation in the international market, the influence of mafia groups in the currency exchange market and their fraudulent propaganda. This study also observes the need for developing strategies, and policies for achieving currency stability, like increasing the balance of exports as compared to imports, preventing the smuggling of foreign reserves, efforts to obtain foreign aid, ensuring political stability, ensuring a congenial environment for internal and external investors, efficient and effective control on monetary and fiscal policy, and preventing mafia groups and their fraudulent propaganda in the currency exchange Markets. The study findings have significant implications for the policymakers to ensure the stability of the Afghan Currency.